2013
DOI: 10.1016/j.antiviral.2013.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Host-targeting agents in the treatment of hepatitis C: A beginning and an end?

Abstract: The development of two distinct classes of hepatitis C antiviral agents, direct-acting antivirals (DAAs) and host-targeting antivirals (HTAs), have distinctly impacted the hepatitis C virus (HCV) field by generating higher sustained virological response (SVR) rates within infected patients, via reductions in both adverse side effects and duration of treatment when compared to the old standard of care. Today DAAs are actively incorporated into the standard of care and continue to receive the most advanced clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 73 publications
(90 reference statements)
0
46
0
Order By: Relevance
“…We showed that the MOBKL1B binding site on NS5A overlapped with the binding site of cyclophilin A (CypA), a cellular protein that is essential for HCV RNA replication, as its interaction with NS5A enhances HCV RNA binding (11)(12)(13)(14). CypA has emerged as the first host factor targeted for anti-HCV therapy, and drugs blocking the CypA-NS5A interaction are currently in various stages of clinical development (15). Mutant HCVs that replicate in the absence of CypA have amino acid substitutions in the CypA binding site of NS5A, and because of the overlap of the MOBKL1B and CypA binding sites, we questioned whether these mutations would also affect NS5A-MOBKL1B interactions.…”
mentioning
confidence: 99%
“…We showed that the MOBKL1B binding site on NS5A overlapped with the binding site of cyclophilin A (CypA), a cellular protein that is essential for HCV RNA replication, as its interaction with NS5A enhances HCV RNA binding (11)(12)(13)(14). CypA has emerged as the first host factor targeted for anti-HCV therapy, and drugs blocking the CypA-NS5A interaction are currently in various stages of clinical development (15). Mutant HCVs that replicate in the absence of CypA have amino acid substitutions in the CypA binding site of NS5A, and because of the overlap of the MOBKL1B and CypA binding sites, we questioned whether these mutations would also affect NS5A-MOBKL1B interactions.…”
mentioning
confidence: 99%
“…HTAs inhibit for example viral entry factors, kinases, micro-RNAs, or enzymes involved in viral replication (reviewed in 63,64 ). Monoclonal antibodies directed against viral entry factors (e.g., CD81-mAbs, anti-SR-BI mAbs, ITX5061), or EGFR kinase (erlotinib) and the cholesterol absorption NPC1L1 inhibitor ezetimibe have been shown to protect or delay HCV infection in mice.…”
Section: Host-targeting Agentsmentioning
confidence: 99%
“…Hepatitis C virus (HCV) infection is a major health problem worldwide, affecting more than 170 million people, and causing viral hepatitis, which often leads to hepatocellular carcinoma [1,2]. In India, HCV genotype 3a is prevalent followed by genotype 1b [3].…”
Section: Introductionmentioning
confidence: 99%